“We do not have a budget”: Evaluating village-level sports programmes for older adults in Aceh - Munzir; Is, Zulheri; Syahputra, Mulyadi (UIR Press, 2026)
Background: Regular physical activity is essential for maintaining health and well-being among older adults. However, despite policy efforts, sport participation among older adults in Aceh remains low, particularly in rural areas. This condition reflects a lack of empirical evidence on how village-level sports programmes are planned, implemented, and evaluated. Objectives: This study aims to evaluate the planning, implementation and evaluation of village-level sports programmes for older adults in Aceh. Methods: A qualitative multiple case study was conducted involving 12 village leaders selected through purposive sampling. Data was collected through semi-structured interviews, observations, and document analysis and analysed using thematic analysis procedures. Results: The findings revealed that the village-level sports programmes are not systematically planned, consistently implemented or critically evaluated. The village-level government dependency on previous programmes, socio-demographic and participant constraints, conceptual and cultural barriers, budget prioritisation bias and informal substitution to the formal planning are the reasons for the programme planning failure. It is implemented mostly event-based, and no evaluation is conducted systematically. Conclusion: The study demonstrates that village-level sports programmes for older adults in Aceh are largely unstructured and lack sustainability due to weak planning and evaluation systems. Strengthening governance and institutional support are essential to improve programme effectiveness.